Consultant outcomes publication and surgical training: Consensus recommendations by the association of surgeons in training. (November 2016) - Mohan, Helen M.; Gokani, Vimal J.; Williams, Adam P.; Harries, Rhiannon L.
Abstract: Consultant Outcomes Publication (COP) has the longest history in cardiothoracic surgery, where it was introduced in 2005. Subsequently COP has been broadened to include all surgical specialties in NHS England in 2013–14. The Association of Surgeons in Training (ASiT) fully supports efforts to improve patient care and trust in the profession and is keen to overcome potential unintended adverse effects of COP. Identification of these adverse effects is the first step in this process: Firstly, there is a risk that COP may lead to reluctance by consultants to provide trainees with the necessary appropriate primary operator experience to become skilled consultant surgeons for the future. Secondly, COP may lead to inappropriately cautious case selection. This adjusted case mix affects both patients who are denied operations, and also limits the complexity of the case mix to which surgical trainees are exposed. Thirdly, COP undermines efforts to train surgical trainees in non-technical skills and human factors, simply obliterating the critical role of the multidisciplinary team and organisational processes in determining outcomes. This tunnel vision masks opportunities to improve patient care and outcomes at a unit level. It also misinforms the public as to the root causes of adverse events by failing to identify care process deficiencies. Finally, for safe surgical care, graduate retention and morale is important – COP may lead to high calibre trainees opting out of surgical careers, or opting to work abroad. The negative effects of COP on surgical training and trainees must be addressed as high quality surgical training and retention of high calibre graduates is essential for excellent patient care.